Heat Shock Protein 90α Is a Potential Serological Biomarker of Acute Rejection after Renal Transplantation. - Takeshi Maehana; Toshiaki Tanaka; Hiroshi Kitamura; Nobuyuki Fukuzawa; Hideki Ishida; Hiroshi Harada; Kazunari Tanabe; Naoya Masumori (PLoS ONE, 2016)
Heat shock protein 90 (HSP90), a molecular chaperone associated with the activation of client proteins, was recently reported to play an important role in immunologic reactions. To date, the role of HSP90 in solid organ transplantations has remained unknown. The aim of this study was to evaluate the relationship between serum HSP90α levels and acute allograft rejection after organ and tissue transplantation using serum samples from kidney allograft recipients, an in vitro antibody-mediated rejection model, and a murine skin transplantation.Serum HSP90α levels were significantly higher in kidney recipients at the time of acute rejection (AR) than in those with no evidence of rejection. In most cases with AR, serum HSP90 decreased to baseline after the treatment. On the other hand, serum HSP90α was not elevated as much in patients with chronic rejection, calcineurin inhibitor nephrotoxicity, or BK virus nephropathy as in AR patients. In vitro study showed that HSP90α concentration in the supernatant was significantly higher in the supernatant of human aortic endothelial cells cocultured with specific anti-HLA IgG under complement attack than in that of cells cocultured with nonspecific IgG. In mice receiving skin transplantation, serum HSP90α was elevated when the first graft was rejected and the level further increased during more severe rejection of the second graft.The results suggest that HSP90α is released into the serum by cell damage due to AR in organ and tissue transplantation, and it is potentially a new biomarker to help detect AR in kidney recipients.